The profile and selected outcomes of coronary artery bypass graft (CABG) patients in the Cape Metropolitan Area : a baseline study - Manie, Shamila (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScPhysio (Physiotherapy))--University of Stellenbosch, 2007.